2016
DOI: 10.5603/gp.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress markers in severe preeclampsia and preeclampsia-related perinatal morbidity — preliminary report

Abstract: Objectives: The aim of the study was to determine maternal serum total antioxidant status (TAS), total oxidant status (TOS), oxidative stress index (OSI), paraoxonase (PON) and arylesterase levels in severe preeclamptic pregnants and also to investigate whether these parameters are implicated in the occurence of perinatal morbidity or not. Material and methods:A case-control study was carried out including 60 pregnant women (30 with severe preeclampsia and 30 healthy controls). The optimal cut off points of ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Nevertheless, the studies included in the meta-analysis related to IMA, UA, and MDA were all consistent with low heterogeneity. Through our search, we also identified other oxidative stress biomarkers including total antioxidant status, total oxidant status, and oxidative stress index, however, the outcomes of these studies were not related to preeclampsia only but included other endpoints such as HELLP syndrome or neurological development [ 43 , 59 , 60 ]. Also, we were unable to obtain a sufficient number of studies (i.e., n < 3) for many biomarkers including total thiol, native thiol, and disulfide, which meant that we could not perform meta-analysis on these.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the studies included in the meta-analysis related to IMA, UA, and MDA were all consistent with low heterogeneity. Through our search, we also identified other oxidative stress biomarkers including total antioxidant status, total oxidant status, and oxidative stress index, however, the outcomes of these studies were not related to preeclampsia only but included other endpoints such as HELLP syndrome or neurological development [ 43 , 59 , 60 ]. Also, we were unable to obtain a sufficient number of studies (i.e., n < 3) for many biomarkers including total thiol, native thiol, and disulfide, which meant that we could not perform meta-analysis on these.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, however, seems to be a concomitant factor in metabolic syndrome, IR and PCOS [ 31 – 33 ]. It was already demonstrated that preeclampsia is a status of elevated oxidative stress [ 10 , 34 ]. Additionally, patients with placental dysfunction are at high risk to develop metabolic syndrome, IR [ 8 ] and cardiovascular disease later in their life [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies in the literature, which show that oxidative stress is extremely high in PIH and that it is in direct positive correlation with values of blood pressure level -with the highest levels of BP, the highest are TBARS values as an oxidative stress marker [10,11,27].…”
Section: Fig1 the Correlation Between Tbars And Cpr In Pregnant Women With Pih And Healthy Pregnant Woomenmentioning
confidence: 99%
“…Free radicals can alter biomolecules, including the unsaturated fatty acids; deoxyribonucleic acid, ribonucleic acid. More recently, great attention has been paid to lipid peroxidation that involves the unsaturated fatty acids and generates several harmful products including malondialdehyde (MDA) [10][11][12]. MDA is the main product of lipid peroxidation and an indicator of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%